2019
DOI: 10.1152/ajplung.00456.2018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and macrophages: driving forces behind exacerbations of asthma and chronic obstructive pulmonary disease?

Abstract: Oxidative stress is a common feature of obstructive airway diseases like asthma and chronic obstructive pulmonary disease (COPD). Lung macrophages are key innate immune cells that can generate oxidants and are known to display aberrant polarization patterns and defective phagocytic responses in these diseases. Whether these characteristics are linked in one way or another and whether they contribute to the onset and severity of exacerbations in asthma and COPD remain poorly understood. Insight into oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 196 publications
0
45
0
3
Order By: Relevance
“…Asthma is an allergic inflammatory respiratory disease. Patients with chronic asthma continuously display chronic inflammation and oxidative stress [8]. Furthermore, pulmonary epithelial cells and immune cells are continuously activated, and they release various inflammatory cytokines, inflammatory mediators, and oxidative molecules that damage cells and tissues, which reduces lung function [6,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Asthma is an allergic inflammatory respiratory disease. Patients with chronic asthma continuously display chronic inflammation and oxidative stress [8]. Furthermore, pulmonary epithelial cells and immune cells are continuously activated, and they release various inflammatory cytokines, inflammatory mediators, and oxidative molecules that damage cells and tissues, which reduces lung function [6,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies pointed out that, in patients with asthma, the airways are stimulated to induce excessive oxidative stress, which aggravates mucus and sputum production and also damages lung cells [48,49]. Asthmatic mouse models and in vitro cellular experiments showed that allergens or inflammatory cytokines could stimulate airway epithelial cell activation, which increased chemokine release, attracted inflammatory immune cell infiltration into the lungs, and induced ROS production in tracheal epithelial cells [8,50]. Animal experiments also showed that these inflamed immune cells released high levels of inflammatory mediators in the lungs and induced oxidative stress, which damaged lung cells and attenuated lung function [51,52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear factor-erythroid 2 p45 subunit-related factor 2 (Nrf2) is essential for activating response in the lung due to induction of the expression of antioxidant and these enzymes are expressed in bronchial and alveolar epithelial cells and macrophages of the lung (8). Several clinical evidences suggested that increased oxidative/nitrosative stress might play a major role in the progression of various lung diseases such as idiopathic pulmonary brosis (IPF), chronic obstructive pulmonary disease, and ARDS (9)(10)(11)(12)(13)(14). HO-1 catalyzes heme degradation to biliverdin-IXα, carbon monoxide, and iron.…”
Section: Introductionmentioning
confidence: 99%